Islamic Arabic Vocabulary in English and Uzbek Languages, Misconceptions and difficulties in translating Arabic- Islamic borrowings from Uzbek into English Language - Sulaymanova Nilufar (International Journal on Integrated Education, 2023)
RESEARCH STATEMENT: This article illustrates the complexities of translating words with Arabic etymology from Uzbek into English in the process of communication. It explores the importance of accurate and careful translation of religious terms in order to facilitate the task of translators and second language learners and deal more efficiently with the challenging language aspects of specific words and expressions. It aims also to assess the difficulties and challenges of translating Arabic Islamic words into English focusing on context and meaning of words in English language. A great number of words from Arabic language remained in Uzbek language as a legacy of the Arab conquest of Central Asia in the early 4 BC. These words present unique challenges as they have deep meanings and often times result in phrases or sentences to literally translate their definition. Therefore, the speakers of Uzbek and Tajik languages may easily understand the translation whereas, the speakers of English language may have difficulties in figuring out what exactly the words mean and in which context. Finally, the students of the English language face certain complexities translating Uzbek words into English or vice-versa while understanding their meaning and trying to at least provide accurate description of their meanings.